Characteristics of Fly Ash from Coal Water Slurry Circulating Fluidized Bed Combustion - ZHANG Daixin; ZHANG Guoqing; LIU Haijun; HUANG Yongbo; DU Shanzhou; FAN Baoguo; HUANG Zhong (Taiyuan Ligong Daxue xuebao)
[Purposes] The content of Al2O3 in the fly ash and slag after combustion of Zhungeer coal is over 45%, which has important value of comprehensive utilization of resources. In order to solve the problems of poor fly ash activity and low Al2O3 extraction efficiency when using Zhungeer coal in conventional circulating fluidized bed boilers, a coal water slurry circulating fluidized bed combustion method was proposed to improve the ash characteristics. [Methods] The effects of feed mode, operating oxygen content, bed temperature, and primary air rate on unburned combustible in fly ash were studied by using a 3 MW circulating fluidized bed combustion test facility, the composition and micro-morphology of fly ash with different particle sizes were analyzed by using specific surface area and pore diameter analysis apparatus, scanning electron microscope, X-ray fluorescence spetrometer, and X-ray diffractometer (XRD). [Findings] The results show that the unburned combustible content in fly ash decreases with the increase of bed temperature, operating oxygen content, and primary air rate, and the unburned combustible content in fly ash in coal water slurry granulated combustion is obviously lower than that in ungranulated combustion. The combustibles in fly ash are mainly below 40 μm, and the unburned combustible content increases with the decrease of fly ash particle size. Most of small fly ash particles were composed of undeveloped pore structure particles with high combustible content. The BET specific surface area and total pore volume decrease with the increase of fly ash particle size, while the average pore size increases gradually, and the total pore volume and the average pore size of the slack coal slurry are smaller than those of the clean coal slurry. It can be found that the content of Al2O3 increases with the decrease of particle size, and the content of Al2O3 in fly ash with particle size less than 15 μm is 51.77%. Acctording to the phase retrieval and semi-quantitative analysis of ash samples, the γ-Al2O3 peak with higher activity is gradually weakened with the increase of particle size, the mullite content is gradually increased with the increase of particle size, and the aluminum extraction efficiency of fly ash decreases. As a whole, in fly ash with particle size less than 50 μm, the content of Al2O3 is higher and the content of mullite is lower, making it more suitable to be used as raw material for aluminum extraction process.